(3OQGSI GdShbs - (3fUjH(B, (3QLes ((3YfGHI(B:s (3OGQ GdYdhe(B,s, 2004)
(3jVe GgejI hGgOGa OQGSI GdShb, Shb GdeDSSI, GdefgGL GdJShjbj, JMdjd Sdhc GdeSJgdc, fXQjI GdGgOGa, GdJaQjY hGdJUfja, WQb hhSGFd OQGSI GdShb, OQGSGJ GdShb GdNGQLj, JbOje fJGFL OQGSI GdShb, OQGSI MGdI GdefJhL GdUfGYj (B((3OQGSI GdShb GdUfGYj(B)(3, eYGdLI fJGFL OQGSI GdShbs
(3HHdjhZQGajG(B: (3U(B. 222-225 (3GdedGMb U(B.226 s
Keywords: (3GdCShGbs; (3GdGMUGA GdJWHjbjs